(untitled) (Global Journal of Science Frontier Research, 2018)
This study is a contribution to the valorisation of neem fruit pulp (Azadirachta indica) to produce bioethanol by alcoholic fermentation. During this study, a physical characterization of neem fruit and physicochemical neem pulp were performed. Also, the variation of the concoction pH of the fermentation tests was carried out in order to find the ideal pH for optimal production of bioethanol by the yeast Saccharomyces cerevisiae. The results obtained show that the pulp represents about 48% of the total mass of neem fruit. And also reveals that the neem pulp is very rich in total sugars (74% for Makabaye and 73% for Baoliwol) and that they can be converted into bioethanol by alcoholic fermentation. The unadjusted wort pH (pH = 5.4) resulted in a maximum bioethanol production of 5.1 mL/100g DM in 05 days of fermentation compared to other fermentation tests (pH = 4.3, 4.5 and 4.7). Also, the distillation of the fermented concoction allowed to obtain bioethanol with an alcohol content of 85% (v / v). This study has shown that neem fruit pulp can be used as an organic material rich in sugars, with a view to intensive production of bioethanol.